2004
DOI: 10.1073/pnas.0307601101
|View full text |Cite
|
Sign up to set email alerts
|

A role for heterodimerization of μ and δ opiate receptors in enhancing morphine analgesia

Abstract: Opiates such as morphine are the choice analgesic in the treatment of chronic pain. However their long-term use is limited because of the development of tolerance and dependence. Due to its importance in therapy, different strategies have been considered for making opiates such as morphine more effective, while curbing its liability to be abused. One such strategy has been to use a combination of drugs to improve the effectiveness of morphine. In particular, ␦ opioid receptor ligands have been useful in enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
412
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(434 citation statements)
references
References 33 publications
(49 reference statements)
12
412
2
1
Order By: Relevance
“…Western blotting have been developed to investigate the existence of heterodimer/heteroligomers in vitro (Gomes et al, 2004;Gomes et al, 2000;Harrison and van der Graaf, 2006;Jordan and Devi, 1999), proving the existence of heteromers in physiological systems has been a more challenging task. Gupta et al (2010) KSA robust for opioid receptor systems, and this would be an important validation criteria for using the model for other G-protein coupled receptor systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting have been developed to investigate the existence of heterodimer/heteroligomers in vitro (Gomes et al, 2004;Gomes et al, 2000;Harrison and van der Graaf, 2006;Jordan and Devi, 1999), proving the existence of heteromers in physiological systems has been a more challenging task. Gupta et al (2010) KSA robust for opioid receptor systems, and this would be an important validation criteria for using the model for other G-protein coupled receptor systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cell studies over more than a decade have suggested that mu opioid receptors (MOPr) and delta opioid receptors (DOPr), as well as kappa opioid receptors (KOPr) and DOPr may exist as heteromers (Gomes et al, 2004;Gomes et al, 2000;Jordan and Devi, 1999). In cell studies, co-expression of KOPr/DOPr heteromers (Jordan and Devi, 1999) or MOPr/DOPr heteromers (Gomes et al, 2004;Gomes et al, 2000) exhibited distinct ligand binding and signaling characteristics compared to cells individually expressing the monomeric form of these receptors, suggesting dimerisation between the different subtypes of opioid receptors could modulate receptor function. More recent studies have focused on conditions that might drive the process of opioid heterodimerisation and evidence has been provided that chronic morphine treatment increases the abundance of heteromers (Gupta et al, 2010), which might be of relevance to the treatment of addiction disorders (Stockton and Devi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of the heroin addiction data, CCU suggested that gene-gene co-association between OPRD1 and OPRM1 and that between OPRD1 and OPRK1 were significant (Table 4), as with LD-based statistic suggesting that SNP-SNP interaction in OPRD1 and OPRM1 was significant but not in OPRD1 and OPRK1. Gene-gene interaction between OPRD1 and OPRM1 had been detected in many studies [34][35][36][37][38][39] and for that between OPRD1 and OPRK1, Jordan and Devi 40 had provided biochemical and pharmacological evidence for the heterodimerization of the two fully functional opioid receptors, which suggests the result of CCU is credible. Analysis of the RA data showed that CCU is much more efficient than traditional logistic regression analysis (Table 5).…”
Section: Characteristics Of Ccu Statisticmentioning
confidence: 97%
“…Studies have demonstrated that opioid receptor dimerization alters signaling (5)(6)(7)(8), trafficking (5,9), and internalization (10). It also has been suggested that opioid receptor heterodimers could explain pharmacological subtypes (3), such as δ 1 (Deltorphin II) respectively, yet, these same subtypes have not been found utilizing cloning methods.…”
Section: Introductionmentioning
confidence: 99%